Pengaruh Brand Image, Brand Trust dan Product Quality terhadap Keputusan Pembelian Produk EcoKing di Kota Batam - Zesvin Zesvin; Nora Pitri Nainggolan (J-MAS (Jurnal Manajemen dan Sains), 2023)
The advancement of digital technology today makes the development of business strategies grow rapidly. So that every company can run its business well, the company continues to strive to develop innovation and creativity to compete in market competition. The purpose of this research is to determine the effect of brand image, brand trust and product quality on purchasing decisions for EcoKing products in Batam City. This study applies a quantitative method by determining a sample of 100 respondents to consumers who are in the city of Batam, specifically the sub-district of Batam, a city that is a user of Ecoking lamp products. Questionnaires are used as a technique in collecting data. With the help of SPSS 26, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of multiple linear regression, brand image (X1) has an effect of 0.231 or 23.1% on purchasing decisions, brand trust (X2) has an effect of 0.424 or 42.4% on purchasing decisions and product quality (X3) has an effect of 0.231 or 23 .1% on purchasing decisions. Brand image, brand trust and product quality factors influence the decision to purchase EcoKing products in Batam City by 67.4% based on the results of the coefficient of determination test. Based on the results of hypothesis testing, it was found that brand image, brand trust and product quality had a positive and significant effect partially or simultaneously on purchasing decisions for EcoKing products in Batam City.